A squaraine-based sensor for colorimetric detection of CO2 gas in an aqueous medium through an unexpected recognition mechanism: experiment and DFT calculation. Issue 48 (4th December 2017) - Sun, Jianqi; Zheng, Xiangjuan; Wu, Xinjie; Li, Dong; Xia, Guomin; Yu, Shuxian; Yu, Qiming; Wang, Hongming
Abstract : A squaraine-based sensor for colorimetric detection of CO2 gas in an aqueous medium through an unexpected recognition mechanism. Abstract : A cationic squaraine-based chemosensorSQM was synthesized and its sensing behaviors towards nucleophiles followed by CO2 gas were described in detail by interpreting the results from UV-Vis, ESI-MS, and 1 H NMR spectral analysis. The results indicated that there were two different paths for the bleaching ofSQM, depending on whether water existed or not when the nucleophilic addition reaction betweenSQM and a superbase, such as TBD or DBU, occurred. More interestingly, the bleachedSQM in MeCN–H2 O (v/v = 90 : 10) could be colorimetrically restored with bubbling CO2 gas, which enabled it to act as a highly sensitive "naked-eye" CO2 gas detector in an aqueous medium. However, when treated in the same way, theSQM bleached in MeCN remained unchanged, unexpectedly. Combining theoretical analysis and experimental tests, a plausible sensing mechanism was proposed to illustrate the bleaching ofSQM and the response of the bleachedSQM to CO2 gas in an aqueous medium.